2014
DOI: 10.1016/j.jacc.2014.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PCSK9 Monotherapy for Hypercholesterolemia

Abstract: In the largest monotherapy trial using a PCSK9 inhibitor to date, evolocumab yielded significant LDL-C reductions compared with placebo or ezetimibe and was well tolerated in patients with hypercholesterolemia. (Monoclonal Antibody Against PCSK9 to Reduce Elevated LDL-C in Subjects Currently Not Receiving Drug Therapy for Easing Lipid Levels-2 [MENDEL-2]; NCT01763827).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
122
1
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 354 publications
(142 citation statements)
references
References 10 publications
7
122
1
5
Order By: Relevance
“…Safety and tolerability profiles in the present study were consistent with previous studies of evolocumab6, 7, 8, 9, 10 and did not identify any risks. No anti‐evolocumab antibodies were detected in any participant.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Safety and tolerability profiles in the present study were consistent with previous studies of evolocumab6, 7, 8, 9, 10 and did not identify any risks. No anti‐evolocumab antibodies were detected in any participant.…”
Section: Discussionsupporting
confidence: 91%
“…The timing and magnitude of LDL‐C lowering after a dose of evolocumab were consistent with those seen in other studies in patients and healthy volunteers 5, 6, 8, 17, 31. For example, the randomized, double‐blind, placebo‐controlled, phase 2 MENDEL study showed that monotherapy with evolocumab 140 mg Q2W in 45 patients with hypercholesterolemia (baseline LDL‐C 3.6 mmol/L) reduced LDL‐C from baseline by 51% (95% CI –56% to –46%) after 12 weeks of treatment 31.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Alirocumab and evolocumab, either alone or in combination with statins and/or other lipid‐lowering therapies, have been shown in their respective phase 3 clinical trial programs (ODYSSEY and PROFICIO [Program to Reduce LDL‐C and Cardiovascular Outcomes Following Inhibition of PCSK9 In Different Populations]) to significantly reduce LDL‐C levels by up to 60% from baseline (depending on dosing regimen; Table) in patients with hypercholesterolemia, including those with familial hypercholesterolemia, moderate to very high cardiovascular risk, and statin intolerance 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62. The inclusion/exclusion criteria and other details of each phase 3 ODYSSEY and PROFICIO trial are shown in Table S2.…”
Section: Pcsk9 Inhibitors and Their Effects In Patients With Diabetesmentioning
confidence: 99%